2014
DOI: 10.1007/s10787-014-0214-z
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use by individuals with multiple sclerosis: effects on specific immune parameters

Abstract: Cannabinoids affect immune responses in ways that may be beneficial for autoimmune diseases. We sought to determine whether chronic Cannabis use differentially modulates a select number of immune parameters in healthy controls and individuals with multiple sclerosis (MS cases). Subjects were enrolled and consented to a single blood draw, matched for age and BMI. We measured monocyte migration isolated from each subject, as well as plasma levels of endocannabinoids and cytokines. Cases met definition of MS by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 70 publications
0
18
0
1
Order By: Relevance
“…Biological aspects affecting cytokines in the synovial fluid and the articular cartilage have recently been studied due to the fact that Cytokines are important factors for treating and preventing osteoarthritis (Kapoor et al, 2011). IL-17has also been widely researched on pathogens and the treatment of multiple sclerosis (Kallaur et al, 2013;Elain et al, 2014;Sexton et al, 2014), systemic lupus erythematosus (Onishi & Gaffen, 2010;Tanasescu et al, 2010), inflammatory bowel disease (Yu et al, 2012;Katz et al, 2014), and psoriasis (Raychaudhuri, 2013;Chiricozzi, 2014). Nevertheless, its relationship with osteoarthritis needs to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…Biological aspects affecting cytokines in the synovial fluid and the articular cartilage have recently been studied due to the fact that Cytokines are important factors for treating and preventing osteoarthritis (Kapoor et al, 2011). IL-17has also been widely researched on pathogens and the treatment of multiple sclerosis (Kallaur et al, 2013;Elain et al, 2014;Sexton et al, 2014), systemic lupus erythematosus (Onishi & Gaffen, 2010;Tanasescu et al, 2010), inflammatory bowel disease (Yu et al, 2012;Katz et al, 2014), and psoriasis (Raychaudhuri, 2013;Chiricozzi, 2014). Nevertheless, its relationship with osteoarthritis needs to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…These probably cause significant stress-responses that are known to be immunosuppressive in EAE (Bolton et al 1997). Importantly, there is no solid data to suggest that doses of medical cannabis cause significant immunosuppressive effects in MS, following analysis of peripheral immune responses (Killestein et al 2003;Katona et al 2005;Sexton et al 2014 (Pryce et al2003;Croxford et al 2008;Webb et al 2008;Hasseldam and Johansen 2010;Hernández-Torres et al 2014;BernalChico et al 2015). In EAE, this is seen by a better functional recovery and a reduced accumulation of disability following paralytic attack Baker et al 2011;Al-Izki et al 2014).…”
Section: Lack Of Marked Immunosuppressive Effects Of Cannabinoids In Eaementioning
confidence: 99%
“…This has also been demonstrated in human subjects who smoke cannabis, indicating that cannabinoids may impair TLR-induced immune activation. [8][9][10] Further, THC has been shown via CB 2 to inhibit the macrophage co-stimulatory signaling required for T-cell activation, thus impairing the adaptive immune response (antibody production and immune memory). 6 Early investigations suggested a TH1 to TH2 shift by cannabinoids, but this has not been replicated in humans with multiple sclerosis-a condition that would benefit from this shift.…”
mentioning
confidence: 99%
“…6 Early investigations suggested a TH1 to TH2 shift by cannabinoids, but this has not been replicated in humans with multiple sclerosis-a condition that would benefit from this shift. 10 Department of Anesthesiology, University of California, San Diego, San Diego, CA, USA. A systems-based analysis of the ECS biologic network revealed that tumor necrosis factor alpha (TNF-a) is one of the major nodes, or units connecting to other signaling units, in the network.…”
mentioning
confidence: 99%
See 1 more Smart Citation